Minocycline black bone disease in arthroplasty: a systematic review - William Steadman; Zak Brown; Christopher J. Wall (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Minocycline black bone disease is a rare finding that can cause concern when unexpectedly encountered during routine arthroplasty. Prolonged minocycline use can cause selective staining of subchondral bone, whilst peri-articular soft tissue and cartilage appear uninvolved. Methods A systematic review according to PRISMA guidelines was performed to identify all reported cases in the literature. Results Including the patient we present, eleven cases of minocycline black bone disease encountered during arthroplasty have been reported in the literature. All cases have had an excellent outcome, with no complications reported to date. Conclusions Minocycline black bone disease can be a concerning intra-operative finding when unexpectedly encountered during routine arthroplasty, but should not affect the operative plan. Surgeons should exclude alternative causes of bone discolouration when the history is unclear.